Proceedings of the Second Conference on Language, Literature, Education, and Culture (ICOLLITE 2018) 2019
DOI: 10.2991/icollite-18.2019.53
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian ELT Teachers’ Beliefs toward Language Learner Autonomy

Abstract: This present study aims at investigating Indonesian EFL teachers' beliefs about learner autonomy. A questionnaire about 36 English teachers' perception towards learner autonomy was used to collect data. The data were analyzed using descriptive analysis by utilizing the SPSS. The study reveals that the majority of Indonesian ELT teachers defined learner autonomy as learners' responsibility for taking care of his own learning independently with less support of the teacher and making decisions about how they lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…A large number of studies report that learner autonomy is essential to be promoted in the EFL classroom (Cheng, 2019;Lengkanawati, 2016;Melvina & Suherdi, 2019;Nguyen, 2011). For instance, showing students how to be autonomous learners will set them up successfully for life.…”
Section: Teacher's Role In Language Learning and Promoting Learner Autonomymentioning
confidence: 99%
“…A large number of studies report that learner autonomy is essential to be promoted in the EFL classroom (Cheng, 2019;Lengkanawati, 2016;Melvina & Suherdi, 2019;Nguyen, 2011). For instance, showing students how to be autonomous learners will set them up successfully for life.…”
Section: Teacher's Role In Language Learning and Promoting Learner Autonomymentioning
confidence: 99%
“…Borg and Al-Busaidi's (2012) questionnaire is seen as a robust instrument to explore teachers' belief regarding language learner autonomy. It had been used in some previous studies (e.g Lengkanawati, 2017;Melvina & Suherdi, 2019;Wichayathian & Reinders, 2018). In this study, EFL teachers' beliefs were gained through a questionnaire covering four perspectives namely technical perspectives, psychological perspectives, political perspectives, and sociocultural perspectives.…”
Section: Methodsmentioning
confidence: 99%
“…One prominent research regarding teachers' beliefs of learner autonomy had been carried out by Borg and Al-Busaidi (2012) which has given important contribution to the field particularly for English Language Teaching. Their questionnaire has been used by many researchers and is recognized as grounded and robust (Lengkanawati, 2017;Melvina & Suherdi, 2019;Wichayathian & Reinders, 2018). Henceforth, with regards to this present study, the researcher decided to use instrument designed by Borg and Al-Busaidi (2012) to obtain the data.…”
Section: Introductionmentioning
confidence: 99%
“…One research found was conducted by Myartawan et al (2013) who explored the relationship between learner autonomy and English proficiency of the first semester students in a university in Bali, Indonesia. Other studies focus more on teacher's belief and practice towards learner autonomy (Agustina, 2017;Lengkanawati, 2016;Melvina & Suherdi, 2019), teachers' and students' perception toward learner autonomy (Khotimah et al, 2019;Ramadhiyah & Lengkanawati, 2019), students' readiness for learner autonomy (Cirocki et al, 2019), and strategies to foster learner autonomy (Yuliani & Lengkanawati, 2017).…”
Section: Learner Autonomy and Language Proficiencymentioning
confidence: 99%